Tanggung Jawab Atas Kebijakan Yang Diterapkan Oleh Perusahaan Induk Kepada Perusahaan Anak Yang Berakibat Pada Timbulnya Suatu Kerugian - Sari Sumantri, Made Gede Niky (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 1 (2020)DO - 10.24843/AC.2020.v05.i01.p15, 2020)
Liability to the parent company for policies implemented by subsidiaries that result in losses with third parties is a major problem in the practice of group. This problem This problem is due to absence of legislation that specifically regulate of the company group, the regulatory framework of the realationship the parent and it’s subsidiaries in the group companies is use Corporate Law. The incorporation of the company’s subsidiary in the group does not abolish  the legal status of a subsidiary. Parent companies in the group company contractions have immunity over the implementation of the principle of limited liability. the purpose of writing this journal is to know, how is the assignment legal liability to the parent company for the policies applied to the subsidiary companies resulting in a loss to a third party and how to anticipate control without legal liability the parent company for its policies that impact the economic insecurity of the subsidiary in the construction of group companies. The research that the author uses is normative legal research. From this research, assigning legal liability to the parent company through the implementation of policies implemented by the subsidiary is certainly seen from the fault that cause losses. One effort that can be done to anticipate control without legal liabilty of the parent companies it’s Make Charter Corporate Relations and Between Subsidiaries or make agreement control between the parent company and subsidiary.